Theories and Practices of Teaching in a Complementary Perspective - Andrukowicz, Wiesław (INSTED: Interdisciplinary Studies in Education & Society, 2011)
In the curriculum of teachers? education two most important trends can be distinguished ? firstly, general humanistic knowledge that allows to actively participate in the culture and which makes it possible to meritorically and formally introduce others into it; secondly, the knowledge and technical and methodological skills that cover tasks and ways of teaching and educating as well as subject methodologies and practices. In order to well organise (at various levels) social life it is necessary to have appropriate predispositions and a good knowledge about history and culture of one?s own and others? societies as well as the ability of applying this knowledge in concrete educational situations, while in order to be able to well organise learning processes it is necessary to have an extensive knowledge about psycho-physical development of a human being and technical and methodological skills, including the newest IT and communication technologies. This is supposed to motivate a teacher to show an organizational initiative and at least, to be flexible and effective while making use of the enormous ?supermarket? of theories. Therefore, why then, since long, has this rather obvious task incurred such various and even opposing solution proposals? Why is a modern teacher not happy about the enormous ?supermarket? of theories?